Strategy Development Of Human Source Competitiveness Strengthening With Learning Media System Analisis Model - -, Fitria; Kurniawan, Hendra; Y, M Ariza Eka (Prosiding International conference on Information Technology and Business (ICITB), 2017)
In this research will Develop Online Teaching Media Application As A Strategy Strengthening Human Resources Competitiveness Facing Globalization. Where the specific purpose of this research is to help the government in its efforts to educate the life of the nation by providing competitiveness and scholarship skills that could only be obtained in college to the graduates of high school and vocational school who can not follow the education in college, whether because of limited funds and because they prefer to work, for free through online teaching media. This online teaching medium will provide various kinds of knowledge required by its users such as Science Management, Accounting, Information Technology or other scholarship for free, in the form of course content, curriculum, teaching videos, and lectures as well as the interaction between teachers and users using office programs. This online teaching media will also work with several university institutions as a form of social responsibility that the academic community gives to their communities to strengthen the competitiveness of Indonesian human resources in ASEAN Community.Â Keywords: Text Media Applications, Analysis Model, and Website.